Design and Experimental Validation of a Re-centring Viscous Dissipater. (February 2018) - Golzar, Farzin G.; Rodgers, Geoffrey W.; Chase, J. Geoffrey
Abstract: The design and experimental validation of a passive, hybrid self-centring supplemental damper for low-damage structures is presented. The device combines rate-dependent dissipation of a viscous damper with the rate-independent dissipation and re-centring restoring force of a ring-spring in a parallel fashion. Experimental proof-of-concept validation tests use sinusoidal displacement inputs consisting of [25, 30] mm amplitudes and [0.25–1.75] Hz frequencies, for two levels of ring-spring pre-load equal to 21% and 34% of the design force. Each component is tested individually to characterise and delineate their specific contributions to the overall device. The ring-spring has a design force capacity of 26 kN and a return stiffness ratio of 34% that remain independent of the velocity input. The viscous device input velocities of [50–330] mm/s provide velocity dependent dissipative forces with a maximum of 22 kN at the maximum input velocity. Individual results in summation match the hybrid device results for the same input, indicating no loss of efficiency in the hybrid device load transfer. Overall, these results offer a range of new, easily implemented options for energy dissipation in developing low-damage structures, which can also provide necessary re-centring capability within the same package. The overall method is readily generalised for a wide range of hybrid device force capacities and design requirements.